Validation of the Career Decision-Making Difficulties Questionnaire Among Korean College Students. (November 2015) - Sovet, Laurent; Tak, Jinkook; Jung, Sungcheol
The purpose of this study was to examine the psychometric properties of the Korean version of the Career Decision-Making Difficulties Questionnaire (CDDQ) among 854 college students. Confirmatory factor analyses partially confirmed the original 10-factor structure of the instrument and demonstrated metric equivalence across gender. The dysfunctional beliefs subscale was particularly inconsistent. Cronbach's α reliabilities ranged from .66 to .88 for the CDDQ subscales and α = .92 for the CDDQ total score. The test–retest reliability for a 1-month interval was .88. The correlation between CDDQ and the Career Decision Self-Efficacy Scale was r = –.54 ( p < .01), which was convergent with previous studies. The undecided college students reported higher CDDQ scores than the decided college students. All the results suggested that CDDQ is a reliable instrument for assessing career decision-making difficulties in the Korean context. Implications for career interventions and research are discussed.